Analisis Gaya Bahasa Dalam Lirik Lagu “Komang” Raim Laode - Setiani, Novi; Izhar , Izhar; Fitriati , Siti (Jurnal Multidisiplin Indonesia, 2023)
This research was conducted to determine the type of language style used in the lyrics of the song "Komang" by Raim Laode. Language style is the way a poet uses language. Language styles are divided into 4, namely comparative language styles, conflicting language styles, linking language styles, and repetition language styles (Tarigan, 2021; 04). This research uses a descriptive qualitative approach. The data source was taken from the lyrics of the song "Komang" by Raim Laode, using the data collection technique of listening, taking notes. Based on the results of the analysis, the researcher found 8 of the 3 types of language styles contained in the lyrics of the song "Komang" by Rain Laode, namely 3 comparative language styles (1 simile, 2 anticipation), 4 conflict language styles (1 hyperbole, 1 hysteron proteron , litoles 1, paradox 1) and 1 linking language style, namely euphemism.